The Concept of Effective Leadership of Madrasah Principals - Sri Mulyani; M. Sirozi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to identify the skills required to be an effective madrasah principal using qualitative methods based on literature review. An effective madrasah principal plays a strategic role in educational management, human resource development, and achieving the goals of quality Islamic education. Therefore, understanding the required skills is crucial to ensuring the effectiveness of their leadership. Through an analysis of various literature, it was found that the required skills include visionary leadership, managerial skills, effective communication, and the ability to manage human resources and finances. Furthermore, madrasah principals are also required to have decision-making skills, the ability to adapt to change, and the ability to create a conducive work climate. The results of this study provide insights for madrasah principals, educators, and related parties in developing training and development programs to improve the quality of leadership in madrasahs.